Two smiling women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two smiling women. The woman on the right is seated on a barstool. Her hand is in the front pocket of the pants of the woman in front of her. The woman on the left has her back to the other woman and is standing between the other woman's legs. She holds a drink in her left hand.